Why Talk with Children Matters: Clinical Implications of Infant- and Child-Directed Speech Research - Ratner, Nan Bernstein (Seminars in Speech and Language, 2013)
This article reviews basic features of infant- or child-directed speech, with particular attention to those aspects of the register that have been shown to impact profiles of child language development. It then discusses concerns that arise when describing adult input to children with language delay or disorder, or children at risk for depressed language skills. The article concludes with some recommendations for parent counseling in such cases, as well as methods that speech-language pathologists can use to improve the quality and quantity of language input to language-learning children.
Keywords: Child-addressed speech; parent-child interaction; child language development; child language disorders; input